The importance of bladder volume in the ultrasound diagnosis of placenta accreta spectrum disorders - Maynard, H; Zamidio, S; Jauniaux, E; Collins, S (Wiley, 2017)
Objective: To assess how a quantifiable measure of vascularity—i.e. abnormal confluence (Acon) in the subplacental myometrium observed by three-dimensional power-Doppler ultrasonography—changes with different bladder volumes. Methods: In a prospective observational study, women referred to a tertiary UK center with suspected PAS disorders were recruited between August 2015 and May 2017. The largest area of confluent three-dimensional power-Doppler signal (Acon) at the uteroplacental interface was estimated under two bladder volumes differing by at least 200 mL. Results: Acon was calculated for 14 women, of whom seven were subsequently found to have PAS disorders. For these seven women, log(Acon) was significantly greater when measured with a filled bladder than when measured with an unfilled bladder (P<0.001). Conclusion: Objective evidence was found for a quantifiable difference in vascularity in the myometrium with bladder volume among women with PAS disorders. This difference has sufficient magnitude to influence the potential of Acon as a diagnostic marker.